The Use of Sodium Sulfacetamide 10%-Sulfur 5% Emollient Foam in the Treatment of Acne Vulgaris - Del Rosso, James Q. (Matrix Medical Communications, 2009)
Acne vulgaris is the most common disorder encountered in ambulatory clinical practice comprising 11.3 percent of office visits to dermatologists in 2005.(1) By comparison, eczematous dermatoses, psoriasis, and skin cancer accounted for 6.2, 3.5, and 10 percent of office visits, respectively.(1) A variety of topical therapeutic options are available for treatment of acne vulgaris, including benzoyl peroxide, antibiotics, retinoids, azelaic acid, and sodium sulfacetamide-sulfur.(2,3) Sodium sulfacetamide 10%-sulfur 5% has been used for the topical treatment of seborrheic dermatitis, acne vulgaris, and rosacea since the mid-1950s and is available in a variety of formulations, including lotions, creams, cleansers, and emollient foams.(4) Recently, an emollient foam sodium sulfacetamide 10%-sulfur 5% formulation indicated for topical therapy of acne vulgaris, rosacea, and seborrheic dermatitis has become available.(5) This article provides an overview of the sodium sulfacetamide 10%-sulfur 5% emollient foam and reports the results of a case report series of patients with acne vulgaris treated with sodium sulfacetamide 10%-sulfur 5% emollient foam as monotherapy or in combination with other topical acne products.